CLINICAL FEATURES AND ANTIMICROBIAL SUSCEPTIBILITIES OF ELIZABETHKINGIA MENINGOSEPTICA - AN EMERGING PATHOGEN FROM A TERTIARY CARE HOSPITAL IN MANGALORE - Venkatesh, Varun; Hegde, Ashwini; M, Radhakrishna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Elizabethkingia meningoseptica has been known to infect the immunocompromised, preterm children, those exposed to antibiotics in critical care units, and those with comorbidities. Multidrug resistance seen in E. meningoseptica makes it daunting to choose the right antimicrobial agents for treating infections caused by this organism. The present study was undertaken to establish the incidence of E. meningoseptica infections, to investigate the clinical features and risk factors associated with these infections, and to study the antimicrobial susceptibility pattern of E. meningoseptica isolates over 2 years. Methods: Medical records of the patient positive for E. meningoseptica from January 2015 to December 2016 were studied retrospectively. The demographic and clinical data of the patients and the antibiotic sensitivity patterns were collected and analyzed. Results: E. meningoseptica was isolated from 13 patients. The mean age was 71.09 years with males being more frequently infected (81.8%). Maximum isolates were from blood (38.5%) with sepsis being the final diagnosis in 53.8% of the patients, followed by respiratory tract infection (46.1%). Two pediatric patients presented with both sepsis and meningitis. Nine patients (69.2%) recovered, and death occurred in four patients (30.8%). Susceptibility testing revealed 100% in vitro resistance to most of the antibiotics such as amikacin, aztreonam, cefepime, ceftazidime, colistin, gentamicin, meropenem, and polymyxin B which are used to treat Gram-negative bacterial infections. The isolates were most susceptible to minocycline and piperacillin. Conclusion: E. meningoseptica is an emerging pathogen and is being isolated more frequently now. An expeditious and prompt institution of appropriate therapy is essential because of its inherent resistance to many antimicrobial agents commonly used to treat infections caused by Gram-negative bacteria.